Self-esteem and its determinants among pulmonary tuberculosis patients in Subang, Indonesia - Setiawan, Hamad; Fadilah, Rurul; Rahmawati, Siti; Pratama, Budi; Kartika, Rina (Program Studi Keperawatan, Politeknik Negeri Subang, 2025)
Background: Pulmonary tuberculosis (TB) significantly affects not only physical health but also the psychological well-being of patients. Self-esteem is a critical aspect of psychological health that influences treatment adherence and recovery. However, limited research has explored the determinants of self-esteem among TB patients in resource-limited settings like Subang, Indonesia. Purpose: This study aimed to examine the factors influencing self-esteem in pulmonary TB patients, focusing on stigma, social support, and economic burden. Methods: A cross-sectional design was employed, involving 150 pulmonary TB patients from Subang, Indonesia. Data were collected using validated instruments to measure self-esteem, stigma, social support, and economic burden. Descriptive and inferential statistical analyses, including correlation and regression, were conducted to identify significant predictors of self-esteem. Results: The mean self-esteem score among participants was 15.4, indicating moderate self-esteem. Stigma was the strongest negative predictor of self-esteem (β = -0.62, p < 0.001), followed by economic burden (β = -0.43, p < 0.001). Social support showed a positive association with self-esteem (β = 0.54, p < 0.001). Demographic variables such as age, employment status, and marital status also influenced self-esteem but to a lesser extent. Conclusion: Self-esteem in TB patients is significantly influenced by stigma, social support, and economic burden. Addressing these factors through integrated care models that reduce stigma, provide financial assistance, and enhance social networks can improve psychological outcomes and treatment adherence among TB patients.